Experimental study on cyclic response of concrete frames reinforced by Steel-CFRP hybrid reinforcement. (February 2021) - Song, Shoutan; Wang, Guan; Min, Xinzhe; Duan, Ning; Tu, Yongming
Abstract: A novel section with Steel-carbon fiber reinforced polymer (CFRP) hybrid reinforcement is introduced. CFRP longitudinal reinforcements are placed in the outer layer of the section, while steel reinforcements are arranged in the inner layer. The new type section is utilized to reduce the residual deformation of anti-seismic structures and improve the durability of structures. Cyclic loading tests are conducted on the four concrete frame structure with an axial compression ratio of 0.31. Seismic performances of concrete frames with steel reinforcements, steel-CFRP hybrid reinforcements and CFRP reinforcements are compared and studied. The major objectives of study are focus on the performance of CFRP reinforcements under the axial compression ratio of 0.31 and the ductility, energy dissipation, strength degradation, unloading stiffness, residual deformation of the frame structure with different reinforcement modes. Test results showed that as compared with the steel reinforced concrete frame, Steel-CFRP hybrid reinforced concrete frame exhibited excellent post-earthquake repairabilities, comparable hysteretic energy dissipation abilities and reasonable strength degradation. Furthermore, when the axial compression ratio is 0.31, the ultimate tensile strength of CFRP reinforcements calculated in accordance with the bearing capacity is 27.2%–32% of the static ultimate tensile strength. The concrete frame with ideal mechanical properties can be obtained by reasonable allocation of steel and CFRP reinforcement. Highlights: Seismic performance of steel-CFRP hybrid reinforced concrete frames were studied. Cyclic loading reduces the limit strength of CFRP reinforcement. The ratio of CFRP reinforcement affects the seismic performance. CFRP reinforcement improves the repairability of concrete frame.